2015
DOI: 10.1016/j.physleta.2015.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field solution of the Blume–Capel model under a random crystal field

Abstract: In this work we investigate the Blume-Capel model with infinite-range ferromag-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…Blume-Capel model is a very useful model due to its simplicity and rich phase diagram. While its phase diagram in the presence of disorder in (T, ∆) plane has been studied using many different techniques like renormalisation group techniques [21], field theories [20],Bethe lattice [22],replica [26] and numerical methods [41], the three field phase diagram has not been studied. In this paper, we found a BEP in the phase diagram of Blume-Capel model with bimodal random crystal field on a fully connected graph by looking at the three field (T, ∆, H) phase diagram.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blume-Capel model is a very useful model due to its simplicity and rich phase diagram. While its phase diagram in the presence of disorder in (T, ∆) plane has been studied using many different techniques like renormalisation group techniques [21], field theories [20],Bethe lattice [22],replica [26] and numerical methods [41], the three field phase diagram has not been studied. In this paper, we found a BEP in the phase diagram of Blume-Capel model with bimodal random crystal field on a fully connected graph by looking at the three field (T, ∆, H) phase diagram.…”
Section: Discussionmentioning
confidence: 99%
“…In two dimensions it was shown that even an infinitesimal amount of random field disorder can change a first order transition to continuous transition or can destroy it altogether [17,18]. Most of the previous studies of random crystal field Blume-Capel model have focussed on (T, ∆) plane [19][20][21][22][23][24][25][26][27]. In this paper, we revisit the problem and look at the phase diagram in the three fields space.…”
mentioning
confidence: 99%
“…For example, the solution obtained using pair approximation [19] does not have the symmetry around p. Similarly, other approximations [16,21], predict a finite transition temperature for all non zero strengths of disorder, which has been proven incorrect by earlier studies using effective field theory [22]. This is because, these treatments deal with only one order parameter (m) and the entropy of zero spin state is not fully accounted for in these approximations.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between quenched disorder provided by a random field and network connectivity in the BC model is investigated by using the replica method [33]. Moreover, the BC model with infinite-range ferromagnetic interactions and under the influence of a quenched disorder has been investigated and a classification of the phase diagrams in terms of their topology is presented in [34].…”
Section: Introductionmentioning
confidence: 99%